Thermal released mercury: a new exploration technology for natural gas hydrate exploration in Tibetan Plateau permafrost area - Zhao, Chaoqing; Tang, Yu; Pang, Shouji; Zhang, Shunyao; Zhang, Fugui (Frontiers in Energy Research, 2025)
The occurrence environment and fundamental characteristics of natural gas hydrate (NGH) in the permafrost regions of the Tibetan Plateau are highly complex. A significant barrier to advancements in NGH exploration within these areas is the lack of effective exploration methods. The Juhugeng mining area represents the sole location in China’s permafrost zone where NGH has been identified. In this study, we conducted a thermal released mercury (TRM) exploration experiment in the Juhugeng area, covering an area of 11.75 km2 with a sampling density of 16 points per square kilometer. Soil samples were collected to a depth of 60 cm, totaling 163 samples, which were analyzed for TRM using the XG-7Z Zeeman mercury analyzer. The experimental results indicate that high-value anomalies of TRM occur at the boundaries of NGH deposits, while lower values are observed directly above the hydrates, forming an annular anomaly pattern. The maximum value of TRM recorded was 127.37 ngg−1, with an average value of 32.59 ngg−1, and the lower limit of the anomaly was established at 39.24 ngg−1. By analyzing the spatial relationship between TRM anomalies and hydrocarbon anomalies, this study proposes a geogas migration mechanism for the formation of TRM anomalies. The anomalies are closely linked to NGH deposits, suggesting that TRM analysis is an effective auxiliary exploration technology for NGH in permafrost regions.